Social Exchange in Mate Selection of Female Migrants in China. Issue 3 (3rd April 2022) - Zeng, Liqun; Liao, Tim F.
Abstract: In China, a critical challenge for rural-to-urban migrants planning to settle down is to convert their rural huko u (household registration) to an urban one through a limited set of de jure channels. This study argues that marriage is a key channel that some migrants take, notably for female migrants. Using data from the 2010 Chinese General Social Survey, we analyzed how educational and age disparities between female rural-to-urban migrants and their husbands relate to urban hukou conversion. We found that the rural women who used marriage as the means to hukou conversion were more likely to marry someone less educated and much older. The findings suggest that rural women can realize their geographical and social mobility by a strategic response to the residence policy, which may in turn impact the dynamics of gender inequality in the household.